Stosowanie dyrektywy Gazowej Unii Europejskiej do podmorskich części gazociągów importowych z państw trzecich – uwagi z punktu widzenia prawa międzynarodowego i Unijnego - Szydło, Marek (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
Energy security of Poland and Ukraine requires that gas pipelines importing natural gas to European Union from third countries, including maritime parts of those pipelines, are subject to EU Third Energy Package, including the EU Gas Directive. The latter body of law aims to ensure precompetitive market environment with third party access to pipelines and ownership unbundling which is strongly favourable to market investments, consumer welfare and security of gas supplies. General international law and EU primary law, as they now stand, make it possible to extend the territorial jurisdiction of EU and, consequently, territorial scope of application of EU law, to some maritime areas belonging to EU Member States, i.e. territorial seas, exclusive economic zones and continental shelves. Thus, international law and primary EU law authorize the actions of EU institutions and EU Member States aiming at extension of EU Third Energy Package to maritime parts of import gas pipelines. It is to be regretted that recently adopted EU Directive 2019/692, amending EU Gas Directive, does not make use of those broader legal entitlements. In view of its specific provisions, EU Directive 2019/692 does not change current de facto derogation from EU Third Energy Package which import gas pipelines still enjoy.
Keywords: bezpieczeństwo energetyczne; gazociągi importowe; dyrektywa gazowa; Konwencja Narodów Zjednoczonych o prawie morza